Climate and base-level controlled fluvial system change and incision during the last glacial–interglacial transition, Roer river, the Netherlands – western Germany. Issue 2 (19th December 2016) - Kasse, C.; Van Balen, R.T.; Bohncke, S.J.P.; Wallinga, J.; Vreugdenhil, M.
Abstract: The fluvial development of the Roer river in the southeastern Netherlands and western Germany is presented for the Late Pleniglacial, Late-glacial and Early Holocene periods. Reconstruction of fluvial-style changes is based on geomorphological and sedimentological analysis. Time control comes from correlation to the pollen-based biochronostratigraphic framework of the Netherlands combined with independent optically stimulated luminescence (OSL) ages. At the Pleniglacial to Late-glacial transition a system and channel pattern change occurred from an aggrading braided to an incising meandering system. Rapid rates of meander migration, as established for the Late-glacial by optical dating, were likely related to the sandy nature of the substratum and the Late-glacial incision of the Meuse that resulted in a higher river gradient in the downstream part of the Roer. In the Roer valley the Younger Dryas cooling is not clearly reflected by a fluvial system response, but this may also be related to Holocene erosion of Younger Dryas fluvial forms. An important incision and terrace formation was established at the Younger Dryas to Early Holocene transition, probably related to forest recovery, reduced sediment supply and base-level lowering of the Meuse. The results of this study show a stepwise reduction in the number of channel courses from a multi-channel braided system in the Pleniglacial, to a double meander-belt system in the Late-glacial and a single-channel meandering system in the Early Holocene. The results show that the forcing factors of fluvial-system change in the Roer valley are climate change (precipitation, permafrost and vegetation) and downstream base-level control by the Meuse.